An Incentory of Tourism Potential in Ngebel Sub-Districts, Ponorogo Regency as a Tourist Center - Fistiana, Inka; Hilman, Yusuf Adam; Triono, Bambang (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
This study examines how the process of inventory activities carried out by the Department of Tourism. The purpose of this study is to find out how the tourism inventory process is carried out by the Department of Tourism and what tourism is contained in Ngebel District. Inventory is an activity carried out to collect data, record and report the results of data collection of state property. The data collection process is carried out by interviewing the Department of Tourism, Local Government and Tourism Managers. The material obtained from interviews was then analyzed and concluded. It can be concluded that many tourism potentials are owned by Ngebel District and the Tourism Office has a standard that is to have a tourist attraction, has adequate facilities and infrastructure, the existence of culinary tourism in these objects. Inventory of tourism potential activities carried out by the Department of Tourism in each field through various stages.